Accidental Organophosphate Poisoning in a Child: A Case Report Highlighting the Importance of Early Recognition and Treatment - Nitari Rahmi Putri; Indra Ihsan (HM Publisher, 2025)
Background: Organophosphate (OP) poisoning is a significant global health concern, especially in developing countries where these chemicals are widely used in agriculture and household pest control. Children are particularly susceptible to accidental OP poisoning due to their inquisitive nature and immature physiology. This case report presents a child with acute muscarinic symptoms following accidental ingestion of an OP insecticide, emphasizing the importance of early recognition and treatment. Case presentation: A 9-year-old boy presented to the emergency department with vomiting, decreased consciousness, and respiratory distress 6 hours after accidentally ingesting an OP insecticide (Baygon) stored in a drinking bottle at home. He exhibited classic muscarinic symptoms, including miosis, hypersalivation, hyperlacrimation, stridor, and wheezing. The patient was treated with atropine and supportive care, resulting in the complete resolution of his symptoms. Conclusion: This case highlights the importance of early recognition and prompt management of OP poisoning in children. Atropine remains the cornerstone of treatment for muscarinic symptoms, and supportive care is crucial to prevent complications. Public health interventions aimed at educating parents and caregivers about the safe storage and handling of OP insecticides are essential to prevent accidental poisoning in children.